238 USE OF A GENERAL MEDICINE CONSULT SERVICE TO EVALUATE AND IMPROVE MEDICAL STUDENT AND RESIDENT KNOWLEDGE OF CONSULTATIVE MEDICINE. (1st January 2005) - Eberhardt, B.; Byrd, E. M.; Byrd, J. C.
Abstract : Background: General internists are frequently asked to provide preoperative consultation for a variety of surgical services. As primary care physicians, they may be faced with assessing their own patients prior to surgical referral. Unfortunately, many medical students and internal medicine residents leave training feeling unequipped to provide quality preoperative consultation. Purpose: We evaluated medical student and resident knowledge of consultative medicine before and after rotating on the General Internal Medicine Consult Service. Methods: A 20-item pretest derived from 14 core articles was administered at the beginning of the rotation. The residents and students read the articles and discussed them formally with their consult faculty during the month-long rotation. A 14-item post-test derived from the same articles was administered at the end of the rotation. Pre- and post-test scores were analyzed using SPSS. Results: Thirty-two percent of the participants were fourth year medical students and 68% were internal medicine residents (R2-R4). Residents performed better on the pretest (p < .0001). Both groups had a significant improvement in knowledge over the month-long course. Students had a greater gain in knowledge 27.8% vs. 19.9% and performed better on the post-test (p < .0001). (table ) Conclusions: Resident and medical student knowledge of consultative medicine is poor. However, their knowledge base improved after completing a 1-month rotation on the General Internal Medicine Consult Service.